2021
DOI: 10.1002/ijfe.2517
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic spillover analysis of international and Turkish food prices

Abstract: This study analyses the dynamic spillover relationship between international and Turkish food prices by employing Markov Switching Regression (MSR) and Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroscedasticity (DCC-GARCH) models to monthly data from 2003 to 2019. We also investigate the factors that cause a price difference between Turkish and international food markets by employing alternative econometric models, including Autoregressive Distributed Lag (ARDL), Fully Modified O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The literature provides some insights into the possible reasons for the periods with bubbles and their relation to Turkey. Food production, CDS spreads, interest rates, fertilizer prices, and raw-material prices, exchange rates, oil prices, fastest growth in exports, low productivity, rising input costs (Agriculture-PPI 2015 = 100 April 2013 index value is 804.64), inflation expectations, demand-side pressures of a growing population, changing consumer preferences, and supply-side elements such as low productivity, dominant players in the retail industry preventing price competitiveness, cost of capital, migration and aging rural populations, low productivity, agricultural education, and problems in the food supply chain are some of the reasons for the formation of food price bubbles [92][93][94][95][96][97][98]. Exchange rates have a strong impact on domestic food prices in countries that are highly dependent on imports of energy, fertilizers, and chemicals [99].…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides some insights into the possible reasons for the periods with bubbles and their relation to Turkey. Food production, CDS spreads, interest rates, fertilizer prices, and raw-material prices, exchange rates, oil prices, fastest growth in exports, low productivity, rising input costs (Agriculture-PPI 2015 = 100 April 2013 index value is 804.64), inflation expectations, demand-side pressures of a growing population, changing consumer preferences, and supply-side elements such as low productivity, dominant players in the retail industry preventing price competitiveness, cost of capital, migration and aging rural populations, low productivity, agricultural education, and problems in the food supply chain are some of the reasons for the formation of food price bubbles [92][93][94][95][96][97][98]. Exchange rates have a strong impact on domestic food prices in countries that are highly dependent on imports of energy, fertilizers, and chemicals [99].…”
Section: Discussionmentioning
confidence: 99%
“…Although oil prices and worldwide food prices have not had a substantial impact, domestic factors such as producer pricing, interest rate, exchange rate and money supply were found to be contributing causes to the high price of food. In a different study, Ertuğrul and Seven (2021) showed that while oil prices lessen the growing gap between Turkish and international food costs, the exchange rate exerted a significant effect on it.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The growing and wealthier global population also have an impact on the production and consumption of agricultural products. Climate change-related global warming can potentially have a detrimental impact on agricultural production and lead to an increase in food costs (Ertuğrul & Seven, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the exchange rate is identified as a critical factor that influences price difference, particularly in times of uncertainty when understanding the impact of exchange rate shocks on domestic prices (Ertugrul & Seven, 2023;Cheikh et al, 2023). Therefore, selecting the appropriate exchange rate regime is an ongoing evaluation that significantly impacts the growth of the business sector and plays a vital role in the development of market economies (Ghosh et al, 2015).…”
Section: The Impact Of Exchange Rate Change On the Hospitality Industrymentioning
confidence: 99%